Atrial Fibrillation and Coronary Artery Disease: A Long-Term Perspective on the Need for Combined Antithrombotic Therapy. (December 2021) - Fanaroff, Alexander C.; Li, Shuang; Marquis-Gravel, Guillaume; Giri, Jay; Lopes, Renato D.; Piccini, Jonathan P.; Wang, Tracy Y.
Abstract : Background: Older adults with atrial fibrillation (AF) are often treated with the shortest possible duration of antiplatelet/anticoagulant therapy after myocardial infarction (MI) or percutaneous coronary intervention (PCI) due to concern for bleeding. However, the risk of recurrent MI or PCI prompting antiplatelet therapy extension is unknown in this population. Methods: Using the National Cardiovascular Data Registry linked to Medicare claims, we described the cumulative incidence of recurrent MI or PCI over a median of 7-year follow-up for patients ≥65 years old with AF discharged alive after acute MI between 2008 and 2017. We used pharmacy fill data to describe the proportion of patients filling prescriptions for both oral anticoagulants and P2Y12 inhibitors for ≥50% of the indicated duration after MI or PCI. Results: Of 187 622 older patients discharged alive after MI, 50 539 (26.9%) had AF. Over a median of 7-year follow-up in patients with AF, the cumulative incidence was 14.5% for recurrent MI, 12.1% for PCI, 7.9% for stroke, and 9.5% for bleeding hospitalization. Among 7998 patients with AF and recurrent MI or PCI, 1668 (20.9%) had >1 MI or PCI during follow-up. Assuming each MI or PCI should be followed by 6 months of P2Y12 inhibitor therapy, patients with AF who had a recurrent MI/PCI had a median estimated indication for antiplatelet/anticoagulant treatment of 287 days (194, 358), but filled both P2Y12 inhibitor and oral anticoagulant for a median of 0 days (0, 21). In this cohort, 12.2% of patients filled prescriptions for both a P2Y12 inhibitor and oral anticoagulant for ≥50% of the indicated duration. Conclusions: Older adults with AF and MI have high incidences of downstream recurrent MI or PCI requiring extended antiplatelet/anticoagulant therapy durations, yet many appear to be under-treated. These results highlight the need for better thrombosis prevention strategies in this group of patients. Abstract : Supplemental Digital Content is available in the text.